Isolating membrane, battery and electric device

By using polymers containing chelating groups and cations in the functional layer of the isolation membrane, the problem of ion migration of metal impurities in the battery is solved, and the reliability and cycle performance of the battery are improved.

CN119340610APending Publication Date: 2025-01-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310905236.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In battery applications, the battery has poor reliability and cycle performance.

Method used

A separation film is used that includes a base material and a functional layer. The functional layer is composed of a polymer, and the polymer contains a chelating group and cations connected to the chelating group through ionic bonds. These chelating groups can chelate with metal impurity ions, and the cations can ion-exchange with metal impurity ions, thereby stabilizing the metal impurity ions and reducing the risk of their migration.

Benefits of technology

By stabilizing metal impurity ions, the reliability of the battery is improved, the self-discharge rate is reduced, and the cycle performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340610A_ABST
    Figure CN119340610A_ABST
Patent Text Reader

Abstract

The invention relates to an isolating membrane, a battery and a power utilization device, the isolating membrane comprises a base material and a functional layer arranged on at least one side of the base material, the functional layer comprises a polymer, and the polymer comprises a chelating group and cations connected to the chelating group through ionic bonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an isolation film, a battery and an electrical device. Background Art

[0002] Batteries have the characteristics of high capacity and long life, so they are widely used in electronic devices, such as mobile phones, laptops, electric vehicles, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes and electric tools, etc. Due to the great progress made in battery cells, higher requirements are placed on the performance of batteries. In order to improve the performance of battery cells, the isolation membrane in the battery is usually optimized and improved.

[0003] However, currently when the separator is used in batteries, the battery reliability and cycle performance are still poor. Summary of the invention

[0004] The present application provides a separation film, a battery and an electrical device, and the use reliability and cycle performance of the battery described in the present application can be improved.

[0005] In a first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer disposed on at least one side of the substrate, wherein the functional layer includes a polymer, and the polymer includes a chelating group and a cation connected to the chelating group by an ion bond.

[0006] Therefore, the isolation membrane in the embodiment of the present application includes an isolation membrane including a substrate and a functional layer arranged on at least one side of the substrate, wherein the functional layer includes a polymer, and the polymer includes a chelating group and a cation connected to the chelating group by an ionic bond. Since the polymer is an organic high molecular material, it has a strong ability to bind to the substrate, so that the functional layer is not easy to separate from the substrate, and the structural stability of the isolation membrane is relatively high; the polymer includes a chelating group and a cation, the chelating group can chelate with the metal impurity ion through a coordination bond, and the cation can exchange with the metal impurity ion, thereby stabilizing the metal impurity ion in the polymer, reducing the risk of the metal impurity ion migrating to the negative electrode plate, and alleviating the risk of the metal impurity ion precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.

[0007] In some embodiments, the chelating group includes at least one of a carboxylic acid group and a sulfonic acid group; optionally, the chelating group includes a carboxylic acid group and a sulfonic acid group. The above-mentioned chelating group includes multiple active sites, and has a stronger coordination ability with metal impurity ions. Through coordination, a chelate is formed. The metal impurity ions can serve as the center of the chelate and be stabilized in the polymer by the chelating group. In particular, when the chelating group includes both a carboxylic acid group and a sulfonic acid group, the polymer can directionally capture the metal impurity ions and adsorb and fix them on the surface of the isolation membrane; the carboxylic acid group and the sulfonic acid group can play a synergistic role due to the enhanced ability of intermolecular coordination of metal impurity ions, and the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0008] In some embodiments, based on the total mass of the polymer, the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group is 0.5:1 to 1:1; alternatively, based on the total mass of the polymer, the mass percentage of the carboxylic acid group is 1% to 15%. Alternatively, based on the total mass of the polymer, the mass percentage of the sulfonic acid group is 1% to 15%. When the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group meets the above range, the synergistic effect of the two is further enhanced, the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0009] In some embodiments, the cations include at least one of alkali metal ions and alkaline earth metal ions; optionally, the alkali metal ions include at least one of lithium ions, sodium ions and potassium ions. Alternatively, the alkaline earth metal ions include at least one of calcium ions and magnesium ions. When the battery cell adopts an alkali metal ion battery, the alkali metal ions can be exchanged with the metal impurity ions, so that the alkali metal ions become free metal ions, which can supplement ions for the battery system and increase the capacity of the battery system.

[0010] In some embodiments, the polymer further comprises an active group, and the active group is connected to the chelating group; optionally, the active group comprises at least one of a carboxylic acid group, an alkenyl group, an epoxy group, a hydroxyl group and an aldehyde group. The above active group is conducive to a grafting reaction with the chelating group, so that the active group and the chelating group are connected, and the chelating group is grafted onto the base polymer.

[0011] In some embodiments, the volume average particle size Dv50 of the polymer is nanometer-level; optionally, the volume average particle size Dv50 of the polymer is 50nm to 200nm; and / or the volume distribution particle size Dv90 of the polymer is 100nm to 250nm. This level of polymer can improve the migration rate of active ions in the battery monomer on the basis of improving the adsorption of metal impurity ions, thereby improving the dynamic performance of the battery monomer.

[0012] In some embodiments, based on the mass of the functional layer, the mass percentage of the polymer is 10% to 50%. When the mass percentage of the polymer is within the above range, the metal impurity ions in the battery monomer system can be effectively adsorbed and stabilized.

[0013] In some embodiments, the coating weight of the functional layer is 1.0 g / m 2 Up to 3.5g / m 2 and / or the thickness of the functional layer may be 0.1 μm to 4 μm, and may be 0.5 μm to 3 μm. When the coating weight or thickness of the functional layer is within the above range, the overall mechanical properties of the isolation film can be improved.

[0014] In some embodiments, the functional layer further comprises heat-resistant particles; optionally, the mass percentage of the heat-resistant particles in the functional layer is less than or equal to 45%. The heat-resistant particles can improve the heat resistance of the isolation film.

[0015] In some embodiments, the thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm; and / or the substrate comprises a polyolefin-based polymer. When the thickness of the functional layer is within the above range, the overall mechanical properties of the isolation membrane can be improved.

[0016] In some embodiments, the substrate may include a polyolefin-based polymer, which has a stronger bonding ability with the functional layer.

[0017] In a second aspect, an embodiment of the present application further provides a battery, wherein the battery comprises an isolation membrane as described in any embodiment of the first aspect of the present application.

[0018] In a third aspect, an embodiment of the present application further proposes an electrical device, comprising a battery as described in any embodiment of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0020] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0021] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0022] Figure 3It is a schematic diagram of an embodiment of a battery module of the present application.

[0023] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0024] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0025] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.

[0026] The drawings are not necessarily drawn to scale.

[0027] The following are the descriptions of the reference numerals:

[0028] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0029] 5. Battery cell; 51. Housing; 52. Electrode assembly;

[0030] 53. Cover plate;

[0031] 6. Electrical equipment. DETAILED DESCRIPTION

[0032] Hereinafter, the embodiments of the isolation membrane, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0033] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0034] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0035] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0036] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0037] The battery cell includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet. The positive electrode sheet includes a positive active material. The positive active material is a donor of active ions such as sodium ions and lithium ions provided by the battery cell. The negative electrode sheet is an acceptor of active ions, and the electrolyte provides a migration path for active ions between the positive electrode sheet and the negative electrode sheet. In the production process of battery cells, the positive electrode active material and / or the electrolyte will inevitably introduce metal impurity ions, for example, at least one of iron ions, copper ions, zinc ions, cadmium ions, chromium ions, manganese ions, cobalt ions, and nickel ions. This part of metal ions usually does not include active ions such as lithium ions, sodium ions, and potassium ions. During the charging process of the battery cell, the metal impurity ions in the positive electrode active material can dissolve in the electrolyte, and the content of the metal impurity ions in the electrolyte increases. The metal impurity ions have a lower reduction potential than the active ions. These metal impurity ions can be embedded in the negative electrode plate in preference to the active ions, reducing the position of the active ion embedding and reducing the reversible capacity of the battery cell; and the metal impurity ions may precipitate on the surface of the negative electrode plate to form metal dendrites. The growth of metal dendrites may pierce the isolation membrane of the battery cell, resulting in direct contact between the positive electrode plate and the negative electrode plate, causing a short circuit, thereby reducing the reliability of the battery cell, and the self-discharge rate of the battery cell is too fast, and the cycle performance of the battery cell is deteriorated.

[0038] In view of the above problems, the embodiment of the present application proposes an isolation membrane, which includes an isolation membrane including a substrate and a functional layer arranged on at least one side of the substrate, wherein the functional layer includes a polymer, and the polymer includes a chelating group and a cation connected to the chelating group by an ionic bond. Since the polymer is an organic high molecular material, it has a strong ability to bind to the substrate, so that the functional layer is not easy to separate from the substrate, and the structural stability of the isolation membrane is relatively high; the polymer includes a chelating group and a cation, the chelating group can chelate with the metal impurity ion through a coordination bond, and the cation can exchange with the metal impurity ion, thereby stabilizing the metal impurity ion in the polymer, reducing the risk of the metal impurity ion migrating to the negative electrode plate, and alleviating the risk of the metal impurity ion precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.

[0039] Isolation film

[0040] In a first aspect, an embodiment of the present application proposes an isolation membrane, which includes a substrate and a functional layer disposed on at least one side of the substrate, wherein the functional layer includes a polymer, and the polymer includes a chelating group and a cation connected to the chelating group by an ion bond.

[0041] The substrate includes two surfaces facing each other along the thickness direction of the isolation film, and the functional layer can be arranged on either one of the two surfaces or on both surfaces.

[0042] The isolation membrane includes a substrate and a functional layer, and the functional layer is arranged on one of the two surfaces of the substrate. In this case, when the isolation membrane is applied to a battery cell, the substrate of the isolation membrane can be arranged closer to the positive electrode sheet relative to the functional layer, that is, the functional layer is located on the side of the substrate away from the positive electrode sheet; or the functional layer of the isolation membrane can be arranged closer to the positive electrode sheet relative to the substrate, that is, the substrate is located on the side of the functional layer away from the positive electrode sheet.

[0043] The polymer can be considered to be a polymer formed by grafting a chelating group on the basis of a base polymer and carrying a cation after being alkalized. The cation and the chelating group can be connected in the form of an ionic bond.

[0044] Since the polymer is an organic high molecular material, it has a strong bonding ability with the substrate, making it difficult for the functional layer to separate from the substrate, and the structural stability of the isolation membrane is relatively high; the polymer includes chelating groups and cations, the chelating groups can chelate with the metal impurity ions through coordination bonds, and the cations can exchange with the metal impurity ions, thereby stabilizing the metal impurity ions in the polymer, reducing the risk of metal impurity ions migrating to the negative electrode plate, and alleviating the risk of metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.

[0045] In some embodiments, the chelating group may include at least one of a carboxylic acid group and a sulfonic acid group. Optionally, the chelating group may include a carboxylic acid group and a sulfonic acid group. The above-mentioned chelating group includes multiple active sites, and has a stronger coordination ability with metal impurity ions. A chelate is formed through coordination. The metal impurity ions can serve as the center of the chelate and are stabilized in the polymer by the chelating group. In particular, when the chelating group includes both a carboxylic acid group and a sulfonic acid group, the polymer can directionally capture the metal impurity ions and adsorb and fix them on the surface of the isolation membrane; the carboxylic acid group and the sulfonic acid group can play a synergistic role due to the enhanced ability of intermolecular coordination of metal impurity ions, and the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0046] In some embodiments, based on the total mass of the polymer, the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group is 0.5: 1 to 1: 1. When the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group meets the above range, the synergistic effect of the two is further enhanced, the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0047] Illustratively, the ratio of the mass percentage of carboxylic acid groups to the mass percentage of sulfonic acid groups can be 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.70:1, 0.75:1, 0.80:1, 0.85:1, 0.90:1, 0.95:1, 1:1 or a range consisting of any two of the above values.

[0048] In some embodiments, the mass percentage of the carboxylic acid group is 1% to 15% based on the total mass of the polymer.

[0049] For example, the mass percentage of the carboxylic acid group can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any two of the above values. When the mass percentage of the carboxylic acid group meets the above range, the synergistic effect with the sulfonic acid group is further enhanced, the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0050] In some embodiments, the mass percentage of the sulfonic acid group is 1% to 15% based on the total mass of the polymer.

[0051] For example, the mass percentage of the sulfonic acid group can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, or a range consisting of any two of the above values. When the mass percentage ratio of the sulfonic acid group meets the above range, the synergistic effect with the carboxylic acid group is further enhanced, the stability of the adsorption of metal impurity ions is improved, and more metal impurity ions can be adsorbed.

[0052] In some embodiments, the cation comprises at least one of an alkali metal ion and an alkaline earth metal ion. Alternatively, the cation may comprise an alkali metal ion.

[0053] Exemplarily, the alkali metal ions may include at least one of lithium ions, sodium ions, and potassium ions.

[0054] Illustratively, the alkaline earth metal ions may include at least one of calcium ions and magnesium ions.

[0055] When the battery cell adopts an alkali metal ion battery, the alkali metal ions can be exchanged with the metal impurity ions, so that the alkali metal ions become free metal ions, which can supplement ions for the battery system and improve the capacity of the battery system. For example, if the battery cell is a lithium ion battery cell, the alkali metal ions can be lithium ions; if the battery cell is a sodium ion battery cell, the alkali metal ions can be sodium ions.

[0056] In some embodiments, the matrix polymer may include an active group; optionally, the active group may include at least one of a carboxylic acid group, an alkenyl group, an epoxy group, a hydroxyl group, and an aldehyde group. The active group is conducive to a grafting reaction with a chelating group, so that the active group and the chelating group are connected, and the chelating group is grafted onto the matrix polymer. The active group and the chelating group can be combined by a covalent bond or the like. On the basis that the matrix polymer includes an active group, the polymer formed thereof also includes an active group.

[0057] In some embodiments, the polymer is also in the form of particles. When the polymer is added to the slurry, the granular polymer can be evenly dispersed in the slurry. The particle size of the polymer has a certain influence on the effect of adsorbing metal impurity ions. When the same mass of polymer is added, the larger the particle size of the polymer, the less the outer surface of the polymer is exposed, the smaller its specific surface area, and the fewer active sites that can bind to metal impurity ions; the smaller the particle size of the polymer, the more outer surface of the polymer is exposed, the larger its specific surface area, the more active sites that can bind to metal impurity ions, and the stronger the ability to adsorb metal impurity ions; however, as the particle size of the polymer decreases, it may block the pore structure of the functional layer, which has a certain influence on the migration of active ions such as lithium ions and sodium ions. The embodiments of the present application take into account the above factors. In some embodiments, the volume average particle size Dv50 of the polymer can be nanometer-level. The polymer of this level can improve the migration rate of active ions in the battery monomer and improve the dynamic performance of the battery monomer on the basis of improving the adsorption of metal impurity ions. Optionally, the volume average particle size Dv50 of the polymer can be 50nm to 200nm. This level of polymer can improve the migration rate of active ions in battery cells while improving the adsorption of metal impurity ions, thereby enhancing the kinetic performance of battery cells.

[0058] Illustratively, the volume average particle size Dv50 of the polymer can be 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, 180nm, 185nm, 190nm, 195nm, 200nm, or a range consisting of any two of the above values.

[0059] In some embodiments, the volume distribution particle size Dv90 of the polymer may be 100 nm to 250 nm. When the volume distribution particle size of the polymer is within the above range, it can make the functional layer thinner and lighter, reduce the overall occupied volume of the separator, and help increase the occupied volume of the positive electrode sheet, the negative electrode sheet, etc., thereby increasing the energy density of the battery cell.

[0060] Illustratively, the volume average particle size Dv90 of the polymer can be 100 nm, 105 nm, 110 nm, 115 nm, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 155 nm, 160 nm, 165 nm, 170 nm, 175 nm, 180 nm, 185 nm, 190 nm, 195 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, or a range consisting of any two of the above values.

[0061] In the embodiment of the present application, the volume average particle size Dv50 of the material has a meaning well known in the art, and the volume average particle size Dv50 of the material refers to the particle size corresponding to 50% in the volume distribution; the volume average particle size Dv90 of the material has a meaning well known in the art, and the volume average particle size Dv90 of the material refers to the particle size corresponding to 90% in the volume distribution. The detection can be carried out using equipment and methods well known in the art. A certain amount of the composite material is taken as a sample, and the volume average particle size Dv50 and Dv90 are tested by a Mastersizer 2000E laser particle size analyzer according to the test standard GB / T 19077-2016.

[0062] In some embodiments, based on the mass of the functional layer, the mass percentage of the polymer can be 10% to 50%. When the mass percentage of the polymer is within the above range, the metal impurity ions in the battery monomer system can be effectively adsorbed and stabilized. Since the number of active groups in the polymer is relatively large, the synergistic effect of carboxylic acid groups and sulfonic acid groups is used to enhance the exchange and adsorption capacity of the polymer for metal impurity ions such as copper, iron, zinc, and cadmium, which can slow down the precipitation of metal impurity ions on the surface of the negative electrode to form metal dendrites and cause the risk of piercing the isolation membrane, improve the physical self-discharge of the battery monomer, improve the K value rate, and improve the battery monomer cycle times and cell safety. At the same time, active ions such as cations in the polymer, such as Li + Separation can also replenish lithium for battery cells.

[0063] Illustratively, the mass percentage of the polymer can be 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50% or a range consisting of any two of the above values.

[0064] In some embodiments, the coating weight of the functional layer is 1.0 g / m 2 Up to 3.5g / m 2 The coating weight of the functional layer refers to the coating weight of the functional layer located on one side of the substrate. When the coating weight of the functional layer is within the above range, the overall mechanical properties of the separator can be improved.

[0065] For example, the coating weight of the functional layer can be 1.0 g / m 2 , 1.2g / m 2 , 1.5g / m 2 , 1.8g / m 2 , 2.0g / m 2 , 2.2g / m 2 , 2.3g / m 2 , 2.5g / m 2 , 2.8g / m 2 , 2.9g / m 2 3.0g / m 2 , 3.1g / m 2 3.2g / m 2 3.3g / m 2 3.4g / m 2 3.5g / m 2 Or a range consisting of any two of the above values.

[0066] In the embodiments of the present application, the coating weight of the functional layer is a well-known meaning in the art and can be tested by methods known in the art. For example, take a single-sided coated isolation film (if it is a double-sided coated isolation film, the functional layer on one side can be wiped off first), punch it into small discs with an area of ​​S1, weigh it, and record it as M1. Then wipe off the functional layer of the isolation film after weighing, weigh the weight of the substrate, and record it as M0. The coating weight of the functional layer = (weight of isolation film M1-weight of substrate M0) / S1.

[0067] In some embodiments, the functional layer may further include heat-resistant particles, which may include inorganic particles. The heat-resistant particles can improve the heat resistance of the isolation film.

[0068] In some embodiments, the mass percentage of the inorganic particles in the functional layer is less than or equal to 45%. For example, the mass percentage of the inorganic particles in the functional layer is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or a range consisting of any two of the above values.

[0069] The inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.

[0070] In some embodiments, inorganic particles having a dielectric constant of 5 or more may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT).

[0071] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass (0<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z Sw , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).

[0072] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0073] In some embodiments, the functional layer may further include a binder. As an example, the binder may include at least one of an aqueous solution type acrylic polymer (e.g., a homopolymer of acrylic acid, methacrylic acid, sodium acrylate monomers or a copolymer with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymer, and polyacrylamide.

[0074] In some embodiments, the thickness of the functional layer may be 0.1 μm to 4 μm, optionally 0.5 μm to 3 μm. When the thickness of the functional layer is within the above range, the overall mechanical properties of the isolation film can be improved. In the present application, the thickness of the functional layer refers to the thickness of the functional layer located on one side of the substrate. Exemplarily, the thickness of the functional layer may be 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or a range consisting of any two of the above values.

[0075] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be 5 μm to 14 μm. The functional layer of the embodiment of the present application is conducive to improving the mechanical properties of the isolation membrane as a whole, so that a thinner substrate can be selected, thereby helping to improve the energy density of the battery cell. Exemplarily, the thickness of the substrate can be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range consisting of any two of the above values.

[0076] In some embodiments, the porosity of the substrate is greater than or equal to 25%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be guaranteed to be conducive to the migration of active ions, and because the porosity is relatively small, the mechanical properties of the substrate can also be guaranteed, providing good support for the functional layer.

[0077] In some embodiments, the substrate may include at least one of a polyolefin-based polymer (e.g., at least one of polyethylene, polypropylene, and polyvinylidene fluoride), a porous glass fiber, and a porous nonwoven fabric. Alternatively, the substrate may include a polyolefin-based polymer, which has a stronger ability to bind to the functional layer. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different. The substrate formed by the above polymer has good chemical stability and mechanical stability.

[0078] It should be noted that the functional layer parameters and functional layer parameters (such as thickness, etc.) of the above-mentioned isolation membrane are all functional layer parameters on one side of the substrate and functional layer parameters on one side of the substrate. When the functional layer parameters are set on both sides of the substrate, the functional layer parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application. When the functional layer parameters are set on both sides of the substrate, the functional layer parameters on either side meet the requirements of this application and are considered to fall within the protection scope of this application.

[0079] Method for preparing isolation film

[0080] In a second aspect, an embodiment of the present application provides a method for preparing an isolation film, the method comprising:

[0081] Step S100, providing a base polymer;

[0082] Step S200, providing a ligand to the base polymer, so that the ligand is grafted to the base polymer through its own chelating group to form an intermediate polymer;

[0083] Step S300, treating the intermediate polymer in an alkaline atmosphere so that the intermediate polymer has cations to obtain a polymer;

[0084] Step S400, disposing a slurry containing the polymer on at least one surface of a substrate, drying the slurry to form a functional layer, and preparing an isolation membrane, wherein the isolation membrane includes a substrate and a functional layer disposed on at least one surface of the substrate.

[0085] According to the method proposed in the embodiment of the present application, the preparation process is simple, and the surface of the prepared isolation membrane includes a polymer, the polymer includes a chelating group and a cation, the chelating group can chelate with the metal impurity ions through a coordination bond, and the cation can exchange with the metal impurity ions, thereby stabilizing the metal impurity ions in the polymer, reducing the risk of the metal impurity ions migrating to the negative electrode plate, and alleviating the risk of the metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.

[0086] In step S100, the base polymer can be made of a variety of materials. In some embodiments, the base polymer can include active groups, such as at least one of carboxylic acid groups, alkenyl groups, epoxy groups, hydroxyl groups, and aldehyde groups. The above active groups are conducive to grafting reactions with chelating groups, so that the active groups and chelating groups are connected, and the chelating groups are grafted onto the base polymer. The active groups and chelating groups can be combined by covalent bonds or the like.

[0087] Illustratively, the base polymer including a carboxylic acid group may include at least one of polyacrylic acid and polybutenoic acid.

[0088] Illustratively, the base polymer including an olefin group may include at least one of polystyrene and polyvinyl pyridine.

[0089] Exemplarily, the base polymer including the epoxy group may include at least one of polypropylene oxide and polyethylene oxide.

[0090] Illustratively, the base polymer including a hydroxyl group may include at least one of a phenolic polymer and a polyphenol.

[0091] Illustratively, the base polymer including an aldehyde group may include at least one of a phenol-formaldehyde polymer and a urea-formaldehyde polymer.

[0092] In step S100, in some embodiments, the matrix polymer can be crushed into particles in advance, for example, by wet grinding; of course, other means such as crushing methods can also be used. The matrix polymer is in a granular state, and the polymer formed based on the matrix polymer is also in a granular state. The polymer is added to the slurry, and the granular polymer can be evenly dispersed in the slurry. In some embodiments, the volume average particle size Dv50 of the polymer can be nanometer-level. This level of polymer can improve the migration rate of active ions in the battery cell while improving the adsorption of metal impurity ions, thereby improving the dynamic performance of the battery cell. Optionally, the volume average particle size Dv50 of the polymer can be 50nm to 200nm.

[0093] In some embodiments, the volume distribution particle size Dv90 of the polymer may be 100 nm to 250 nm. When the volume distribution particle size of the polymer is within the above range, it can make the functional layer thinner and lighter, reduce the overall occupied volume of the separator, and help increase the occupied volume of the positive electrode sheet, the negative electrode sheet, etc., thereby increasing the energy density of the battery cell.

[0094] In step S200, in some embodiments, the chelating group may include at least one of a carboxylic acid group and a sulfonic acid group. Alternatively, the chelating group may include a carboxylic acid group and a sulfonic acid group. The above-mentioned chelating group includes multiple active sites, and has a stronger coordination ability with the metal impurity ions. A chelate is formed through coordination, and the metal impurity ions can serve as the center of the chelate and be firmly fixed in the polymer by the chelating group. In particular, when the chelating group includes both a carboxylic acid group and a sulfonic acid group, the carboxylic acid group and the sulfonic acid group can play a synergistic role to improve the adsorption of the metal impurity ions.

[0095] In some embodiments, the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group is 0.5:1 to 1:1 based on the total mass of the polymer.

[0096] In some embodiments, the mass percentage of the carboxylic acid group is 1% to 15% based on the total mass of the polymer.

[0097] In some embodiments, the mass percentage of the sulfonic acid group is 1% to 15% based on the total mass of the polymer.

[0098] When the chelating group includes a carboxylic acid group and a sulfonic acid group, the sulfonic acid group and the carboxylic acid group may be grafted sequentially. Of course, the carboxylic acid group and the sulfonic acid group may also be grafted sequentially. Different chelating groups may be grafted sequentially by repeating steps S200 and S300.

[0099] Next, we will take the sequential grafting of sulfonic acid groups and carboxylic acid groups as an example for illustrative explanation:

[0100] A ligand containing a sulfonic acid group is provided to a base polymer, and a sulfonation treatment is performed to graft the sulfonic acid group onto the base polymer to obtain a first intermediate polymer; wherein the molar ratio of the base polymer, such as polystyrene, to the sulfonating agent is 1:1-4; the reaction temperature is 50-70°C; the reaction time is 1-5 hours; the sulfonating agent can be a composite system of SO3 gas or SO3 / alkyl phosphate (mass ratio is 3:1);

[0101] Treating the first intermediate polymer with a 2% to 6% sodium hydroxide aqueous solution to adjust the system pH to 7 to 8, and replacing the hydrogen ions of the sulfonic acid groups in the first intermediate polymer with sodium ions in the sodium hydroxide so that the first intermediate polymer carries cations, namely sodium ions;

[0102] The first intermediate polymer having sodium ions is dried, and the first intermediate polymer after drying is grafted with acrylic acid monomer under ultraviolet light conditions, so that the first intermediate polymer is grafted with carboxylic acid groups, thereby obtaining a second intermediate polymer.

[0103] The second intermediate polymer is treated with a 2% to 6% sodium hydroxide aqueous solution to adjust the system pH to 7 to 8, and the hydrogen ions of the carboxylic acid groups in the second intermediate polymer are replaced by sodium ions in the sodium hydroxide, so that the second intermediate polymer carries cations, namely sodium ions.

[0104] The second intermediate polymer carrying the cation is soaked in 2% to 6% hydrochloric acid for 3 to 4 hours to neutralize excess sodium hydroxide aqueous solution, and then washed with deionized water for 2 to 4 hours to obtain a polymer.

[0105] When the battery cell is a lithium-ion battery, the polymer can be further treated with a 2% to 6% lithium hydroxide aqueous solution to replace the sodium ions in the polymer with lithium ions, and the polymer can be washed with deionized water to make the system neutral. When the polymer is applied to the isolation membrane, the lithium ions in the polymer can be exchanged with the metal impurity ions, so that the lithium ions in the polymer form free lithium ions, which can replenish lithium for the battery system. Of course, if the battery cell is a sodium-ion battery, this operation can be omitted. The sodium ions carried in the polymer can also replenish sodium for the battery system and increase the sodium ion content in the system.

[0106] In other embodiments, the intermediate polymer may also be treated in an alkaline atmosphere using other alkaline substances, such as lithium hydroxide, potassium hydroxide, calcium hydroxide, magnesium hydroxide, and the like.

[0107] In step S400, in some embodiments, based on the mass of the functional layer, the mass percentage of the polymer may be 10% to 50%. When the mass percentage of the polymer is within the above range, the metal impurity ions in the battery monomer system can be effectively adsorbed and stabilized.

[0108] In some embodiments, the coating weight of the functional layer is 1.0 g / m 2 Up to 3.5g / m 2 The coating weight of the functional layer refers to the coating weight of the functional layer located on one side of the substrate. When the coating weight of the functional layer is within the above range, the overall mechanical properties of the separator can be improved.

[0109] polymer

[0110] In a third aspect, an embodiment of the present application provides a polymer, which includes a chelating group and a cation connected to the chelating group by an ion bond.

[0111] In some embodiments, the chelating group may include at least one of a carboxylic acid group and a sulfonic acid group. Alternatively, the chelating group may include a carboxylic acid group and a sulfonic acid group.

[0112] In some embodiments, the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group is 0.5:1 to 1:1 based on the total mass of the polymer.

[0113] In some embodiments, the mass percentage of the carboxylic acid group is 1% to 15% based on the total mass of the polymer.

[0114] In some embodiments, the mass percentage of the sulfonic acid group is 1% to 15% based on the total mass of the polymer.

[0115] In some embodiments, the cation includes at least one of an alkali metal ion and an alkaline earth metal ion. Alternatively, the cation may include an alkali metal ion.

[0116] In some embodiments, the polymer may include an active group; optionally, the active group may include at least one of a carboxylic acid group, an olefinic group, an epoxy group, a hydroxyl group, and an aldehyde group.

[0117] In some embodiments, the volume average particle size Dv50 of the polymer may be nanometer-sized; alternatively, the volume average particle size Dv50 of the polymer may be 50 nm to 200 nm.

[0118] In some embodiments, the volume distribution particle size Dv90 of the polymer may be from 100 nm to 250 nm.

[0119] Battery Cell

[0120] In a fourth aspect, an embodiment of the present application provides a battery cell, wherein the battery cell includes a separator. The separator may include a separator according to any embodiment of the first aspect of the present application or a separator prepared by a method according to any embodiment of the second aspect of the present application, and the separator serves to isolate the positive electrode sheet from the negative electrode sheet. By using the separator, the reliability, self-discharge performance, and cycle performance of the battery cell can be improved.

[0121] [Positive electrode]

[0122] In some embodiments, the battery cell further includes a positive electrode tab.

[0123] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.

[0124] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0125] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0126] In some embodiments, the positive electrode active material may be a positive electrode active material for a battery cell known in the art. As an example, the positive electrode active material may include at least one of the following materials, a layered positive electrode active material (e.g., ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material, a spinel structured positive electrode active material (e.g., spinel lithium manganate, spinel nickel lithium manganate, lithium-rich spinel lithium manganate, and lithium nickel lithium manganate, etc.).

[0127] For example, the general formula of the layered positive electrode active material is Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the layered positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, and the like.

[0128] Optionally, the layered positive electrode active material is a ternary material, for example, 0<a≤1, 0<b≤1, 0<c≤1, illustratively, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811) and LiNi 0.5 Co 0.2Mn 0.3 O2 (NCM523) or more.

[0129] For example, the general formula of the olivine phosphate active material is Li x A y Me a M b P 1-c X c Y z , wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.

[0130] For example, the general formula of the positive electrode active material of the spinel structure is Li x A y Mn a M 2-a Y z , wherein 0≤x≤2, 0≤y≤1, and 0.9≤x+y≤2; 0.5≤a≤2; 3≤z≤5; A includes one or more of Na, K, and Mg; M includes one or more of Ni, Co, B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; and Y includes one or more of O and F. Specifically, the positive active materials of the spinel structure include LiMn2O4, LiNi 0.5 Mn 1.5 O4、LiCr 0.3 Mn 1.7 O4、Li 1.1 Al 0.1 Mn 1.9 O4, Li2Mn2O4 and Li 1.5 One or more of Mn2O4.

[0131] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.

[0132] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.

[0133] In some embodiments, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate polymer.

[0134] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0135] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0136] [Negative electrode]

[0137] In some embodiments, the battery cell further includes a negative electrode tab.

[0138] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0139] The negative electrode active material may be a negative electrode active material for a battery cell known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.

[0140] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The embodiment of the present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5wt%.

[0141] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The embodiment of the present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated polymer SR-1B, aqueous acrylic polymer (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5wt%.

[0142] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2wt%.

[0143] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0144] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0145] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the embodiments of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some other embodiments, the negative electrode plate described in the embodiments of the present application further includes a protective layer covering the surface of the negative electrode film layer.

[0146] [Electrolyte]

[0147] In some embodiments, the battery cell may further include an electrolyte.

[0148] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The embodiment of the present application has no particular limitation on the type of electrolyte, which can be selected according to actual needs.

[0149] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.

[0150] When the battery cell of an embodiment of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0151] When the battery cell of an embodiment of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0152] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0153] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.

[0154] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.

[0155] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.

[0156] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0157] The present application has no particular restrictions on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.

[0158] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0159] The preparation method of the battery cell of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0160] In some embodiments of the present application, the battery cells according to the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.

[0161] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0162] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0163] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0164] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0165] The battery according to the embodiment of the present application may include one battery cell or a plurality of battery cells. When the battery includes a plurality of battery cells, the battery may include a battery module or a battery pack.

[0166] Electrical devices

[0167] The fifth aspect of the embodiment of the present application provides an electric device, which includes at least one of the battery cells, battery modules or battery packs of the present application. The battery cells, battery modules or battery packs can be used as the power source of the electric device, and can also be used as the energy storage unit of the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0168] The electrical device may select a battery cell, a battery module or a battery pack according to its usage requirements.

[0169] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.

[0170] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0171] Example

[0172] The following embodiments describe the contents disclosed in the present application in more detail, and these embodiments are only used for illustrative explanations, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the present application disclosure. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0173] Preparation of Lithium Ion Batteries in Examples and Comparative Examples

[0174] 1. Preparation of positive electrode sheet

[0175] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0176] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone NMP at a weight ratio of 97.5:1.4:1.1 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.

[0177] 2. Preparation of negative electrode sheet

[0178] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0179] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.

[0180] 3. Isolation film

[0181] (1) First, 100 g of polystyrene resin was weighed and prepared by wet grinding (using a mass ratio of zirconia balls to polystyrene resin of 5:1, a particle size of zirconia balls of 1 mm, grinding time of 5 h, and a ball mill speed of 500 r / min) to obtain polystyrene;

[0182] (2) 100 g of sub-nano polystyrene prepared in step (1) is subjected to sulfonation treatment to obtain a first intermediate polymer; the first intermediate polymer is then subjected to alkalization treatment with a 4% sodium hydroxide aqueous solution for 4 h; wherein the molar ratio of polystyrene to sulfonating agent is 1:4; the reaction temperature is 60° C.; the reaction time is 3 h; the sulfonating agent can be a mixture of SO3 / methyl phosphate (mass ratio is 3:1);

[0183] (3) The first intermediate polymer after alkalization treatment in step (2) was vacuum dried at 60° C. for 5 h, and then the first intermediate polymer was surface treated by ultraviolet light grafting to graft acrylic acid monomer for 20 seconds at 60° C. to obtain a second intermediate polymer; and then alkalized with 4% sodium hydroxide aqueous solution for 3 h;

[0184] (4) soaking the second intermediate polymer after alkalization treatment in step (3) in 3% hydrochloric acid for 3 hours, and then washing with deionized water for 2 hours; then soaking the resin in 2% lithium hydroxide aqueous solution for 3 hours, and then washing with deionized water until neutral, to prepare a polymer;

[0185] (5) Weigh 100 g of the polymer obtained in step (4) and add it to 1000 g of CCS slurry (solid content of 45% aluminum oxide aqueous solution), stir evenly, and evenly coat the CCS slurry containing the polymer on both surfaces of a polypropylene PP substrate (12 μm). Dry the CCS slurry to form a functional layer to obtain a separator. The coating weight of the single-sided functional layer is 2±0.05 g / m 2 .

[0186] 4. Preparation of electrolyte

[0187] In an environment where the water content is less than 10 ppm, organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0188] 5. Preparation of battery cells

[0189] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0190] Example 1

[0191] The above steps are adopted to prepare a lithium ion battery.

[0192] Comparative Example 1

[0193] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the isolation membrane was prepared by the following steps:

[0194] CCS slurry (solid content of 45% aluminum oxide aqueous solution) was evenly coated on both surfaces of a polypropylene PP substrate (12 μm), and the CCS slurry was dried to form a functional layer to obtain an isolation film. The coating weight of the single-sided functional layer was 2±0.05 g / m 2 .

[0195] Example 2-1 to Example 2-7

[0196] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the types and contents of the chelating groups in the functional layer of the isolation membrane were adjusted in Examples 2-1 to 2-7.

[0197] Example 3-1 to Example 3-3

[0198] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the type of the matrix polymer of the functional layer in the isolation membrane was adjusted in Examples 3-1 to 3-3.

[0199] Example 4-1 to Example 4-4

[0200] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 is that the particle size of the polymer in the isolation membrane was adjusted in Examples 4-1 to 4-4. The specific preparation steps are as follows:

[0201] In Example 4-1,

[0202] (1) First, 100 g of polystyrene resin was weighed and prepared by wet grinding (using a mass ratio of zirconia balls to polystyrene resin of 5:1, a particle size of zirconia balls of 1 mm, grinding time of 12 h, and a ball mill speed of 500 r / min) to obtain polystyrene;

[0203] (2) 100 g of sub-nano polystyrene prepared in step (1) is subjected to sulfonation treatment to obtain a first intermediate polymer; and then subjected to alkalization treatment with a 4% sodium hydroxide aqueous solution for 4 h; wherein the molar ratio of polystyrene to sulfonating agent is 1:4; the reaction temperature is 60° C.; the reaction time is 3 h; and the sulfonating agent can be a mixture of SO3 / alkyl phosphate ester in a mass ratio of 3:1;

[0204] (3) The first intermediate polymer after alkalization treatment in step (2) was vacuum dried at 60° C. for 5 h, and then the first intermediate polymer was surface treated by ultraviolet light grafting to graft acrylic acid monomer for 20 seconds at 60° C. to obtain a second intermediate polymer; and then alkalized with 4% sodium hydroxide aqueous solution for 3 h;

[0205] (4) soaking the second intermediate polymer after alkalization treatment in step (3) in 3% hydrochloric acid for 3 hours, and then washing with deionized water for 2 hours; then soaking the resin in 2% lithium hydroxide aqueous solution for 3 hours, and then washing with deionized water until neutral, to prepare a polymer;

[0206] (5) Weigh 100 g of the polymer obtained in step (4) and add it to 1000 g of CCS slurry (solid content of 45% aluminum oxide aqueous solution), stir evenly, and evenly apply the CCS slurry containing the polymer on both surfaces of a polypropylene PP substrate (12 μm). Dry the CCS slurry into a functional layer to obtain an isolation membrane.

[0207] In Example 4-2,

[0208] (1) First, 100 g of polystyrene resin was weighed and wet-milled (using a mass ratio of 5:1 of zirconia balls to polystyrene resin, a particle size of 1 mm, a grinding time of 8 h, and a ball mill speed of 500 r / min) to obtain subnano polystyrene with a Dv50 of 100 nm and a Dv90 of 123 nm;

[0209] (2) 100 g of sub-nano polystyrene prepared in step (1) is subjected to sulfonation treatment to obtain a first intermediate polymer; and then subjected to alkalization treatment with a 4% sodium hydroxide aqueous solution for 4 h; wherein the molar ratio of polystyrene to sulfonating agent is 1:4; the reaction temperature is 60° C.; the reaction time is 3 h; and the sulfonating agent can be a mixture of SO3 / alkyl phosphate ester in a mass ratio of 3:1;

[0210] (3) The first intermediate polymer after alkalization treatment in step (2) was vacuum dried at 60° C. for 5 h, and then the first intermediate polymer was surface treated by ultraviolet light grafting to graft acrylic acid monomer for 20 seconds at 60° C. to obtain a second intermediate polymer; and then alkalized with 4% sodium hydroxide aqueous solution for 3 h;

[0211] (4) soaking the second intermediate polymer after alkalization treatment in step (3) in 3% hydrochloric acid for 3 hours, and then washing with deionized water for 2 hours; then soaking the resin in 2% lithium hydroxide aqueous solution for 3 hours, and then washing with deionized water until neutral, to prepare a polymer;

[0212] (5) Weigh 100 g of the polymer obtained in step (4) and add it to 1000 g of CCS slurry (solid content of 45% aluminum oxide aqueous solution), stir evenly, and evenly apply the CCS slurry containing the polymer on both surfaces of a polypropylene PP substrate (12 μm). Dry the CCS slurry into a functional layer to obtain an isolation membrane.

[0213] In Example 4-3,

[0214] (1) First, 100 g of polystyrene resin was weighed and wet-milled (using a mass ratio of zirconia balls to polystyrene resin of 5:1, a particle size of zirconia balls of 1 mm, a grinding time of 6 h, and a ball mill speed of 500 r / min) to obtain sub-nano polystyrene with a Dv50 of 100 nm and a Dv90 of 123 nm;

[0215] (2) 100 g of sub-nano polystyrene prepared in step (1) is subjected to sulfonation treatment to obtain a first intermediate polymer; and then subjected to alkalization treatment with a 4% sodium hydroxide aqueous solution for 4 h; wherein the molar ratio of polystyrene to sulfonating agent is 1:4; the reaction temperature is 60° C.; the reaction time is 3 h; and the sulfonating agent can be a mixture of SO3 / alkyl phosphate ester in a mass ratio of 3:1;

[0216] (3) The first intermediate polymer after alkalization treatment in step (2) was vacuum dried at 60° C. for 5 h, and then the first intermediate polymer was surface treated by ultraviolet light grafting to graft acrylic acid monomer for 20 seconds at 60° C. to obtain a second intermediate polymer; and then alkalized with 4% sodium hydroxide aqueous solution for 3 h;

[0217] (4) soaking the second intermediate polymer after alkalization treatment in step (3) in 3% hydrochloric acid for 3 hours, and then washing with deionized water for 2 hours; then soaking the resin in 2% lithium hydroxide aqueous solution for 3 hours, and then washing with deionized water until neutral, to prepare a polymer;

[0218] (5) Weigh 100 g of the polymer obtained in step (4) and add it to 1000 g of CCS slurry (solid content of 45% aluminum oxide aqueous solution), stir evenly, and evenly coat the CCS slurry containing the polymer on both surfaces of a polypropylene PP substrate (12 μm). Dry the CCS slurry to form a functional layer to obtain a separator. The coating weight of the single-sided functional layer is 2±0.05 g / m 2 .

[0219] In Example 4-4,

[0220] (1) First, 100 g of polystyrene resin was weighed and prepared by wet grinding (using a mass ratio of zirconia balls to polystyrene resin of 5:1, a particle size of zirconia balls of 1 mm, grinding time of 4.5 h, and a ball mill speed of 500 r / min) to obtain polystyrene;

[0221] (2) 100 g of sub-nano polystyrene prepared in step (1) is subjected to sulfonation treatment to obtain a first intermediate polymer; and then subjected to alkalization treatment with a 4% sodium hydroxide aqueous solution for 4 h; wherein the molar ratio of polystyrene to sulfonating agent is 1:4; the reaction temperature is 60° C.; the reaction time is 3 h; and the sulfonating agent can be a mixture of SO3 / alkyl phosphate ester in a mass ratio of 3:1;

[0222] (3) The first intermediate polymer after alkalization treatment in step (2) was vacuum dried at 60° C. for 5 h, and then the first intermediate polymer was surface treated by ultraviolet light grafting to graft acrylic acid monomer for 20 seconds at 60° C. to obtain a second intermediate polymer; and then alkalized with 4% sodium hydroxide aqueous solution for 3 h;

[0223] (4) soaking the second intermediate polymer after alkalization treatment in step (3) in 3% hydrochloric acid for 3 hours, and then washing with deionized water for 2 hours; then soaking the resin in 2% lithium hydroxide aqueous solution for 3 hours, and then washing with deionized water until neutral, to prepare a polymer;

[0224] (5) Weigh 100 g of the polymer obtained in step (4) and add it to 1000 g of CCS slurry (solid content of 45% aluminum oxide aqueous solution), stir evenly, and evenly apply the CCS slurry containing the polymer on both surfaces of a polypropylene PP substrate (12 μm). Dry the CCS slurry into a functional layer to obtain an isolation membrane.

[0225] Example 5-1 to Example 5-4

[0226] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the mass percentage of the polymer in the isolation membrane was adjusted in Examples 5-1 to 5-4.

[0227] Example 6-1 to Example 6-3

[0228] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the coating weight of the functional layer in the isolation film was adjusted in Examples 6-1 to 6-3.

[0229] The relevant parameters of the embodiments and comparative examples are shown in Table 1.

[0230] Test Section

[0231] 1. Cycle performance test of lithium-ion batteries

[0232] At 25°C, the lithium-ion battery is charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V constant voltage, and then discharged to 2.8V at 1C constant current. This is a charge and discharge cycle. Taking the capacity of the first discharge as 100%, calculate the capacity retention rate of the battery after 500 cycles. The capacity retention rate of the battery after 500 cycles (%) = discharge capacity of the 500th cycle / capacity of the first discharge × 100%.

[0233] 2. K value test

[0234] The K value can be used to describe the physical quantity of the self-discharge rate of a battery cell. It can be calculated by dividing the open circuit voltage difference between two tests by the time interval △t between the two voltage tests. The formula is: K = (OCV2-OCV1) / △t. That is, K can represent the voltage drop per unit time. Generally speaking, the larger the K value, the faster the open circuit voltage drops or the larger the amplitude is, and there may be a micro-short circuit in the battery cell.

[0235] 3. ICP test of metal ion content in electrolyte

[0236] ICP instrument model: ICAP 7200ICP-OES, manufactured by ThermoFisher Technology (formerly Thermo Fisher Scientific);

[0237] Test conditions: The sample must be an electrolyte liquid. If it contains solid particles, it needs to be digested with acid or filtered to remove the solid particles. The range of the measured elements must be within the range of the standard curve. If it exceeds the range, the sample needs to be diluted.

[0238] Main operating procedures: 1. Test standard curve; 2. Dilute the sample to be tested; 3. Test the diluted sample; 4. Calculate and process the data to obtain the concentration of the element to be tested.

[0239] The electrolyte in a fresh battery cell is taken as a sample and tested by an inductively coupled plasma spectrometer ICP. A fresh battery cell refers to a battery cell that has been cycled less than 10 times.

[0240] Test Results

[0241] The test results are shown in Table 1

[0242] Table 1

[0243]

[0244]

[0245] In Table 1, the K value represents the K value obtained by testing at a time interval of 14 days.

[0246] It can be seen from Table 1 that, compared with Comparative Example 1, the functional layer of the isolation membrane of the embodiment of the present application includes a polymer. Since the polymer is an organic high molecular material, it has a strong bonding ability with the substrate, so that the functional layer is not easy to separate from the substrate, and the structural stability of the isolation membrane is relatively high; the polymer includes a chelating group and a cation. The chelating group can chelate with the metal impurity ions through a coordination bond, and the cation can exchange with the metal impurity ions, thereby stabilizing the metal impurity ions in the polymer, reducing the risk of the metal impurity ions migrating to the negative electrode plate, and alleviating the risk of the metal impurity ions precipitating on the surface of the negative electrode plate to form metal dendrites, thereby improving the reliability of the battery cell; thereby, the self-discharge rate of the battery cell can be reduced, and the cycle performance of the battery cell can be improved.

[0247] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. A separator, comprising a substrate and a functional layer disposed on at least one side of the substrate, wherein the functional layer comprises a polymer, and the polymer comprises a chelating group and a cation connected to the chelating group by an ion bond.

2. The isolation film according to claim 1, wherein: The chelate group includes at least one of a carboxylic acid group and a sulfonic acid group; Optionally, the chelating group includes a carboxylic acid group and a sulfonic acid group.

3. The isolation film according to claim 2, wherein: Based on the total mass of the polymer, the ratio of the mass percentage of the carboxylic acid group to the mass percentage of the sulfonic acid group is 0.5:1 to 1:1; Optionally, based on the total mass of the polymer, the mass percentage of the carboxylic acid group is 1% to 15%; Optionally, based on the total mass of the polymer, the mass percentage of the sulfonic acid group is 1% to 15%.

4. The separator according to any one of claims 1 to 3, wherein: The cations include at least one of alkali metal ions and alkaline earth metal ions; Optionally, the alkali metal ions include at least one of lithium ions, sodium ions and potassium ions; Optionally, the alkaline earth metal ions include at least one of calcium ions and magnesium ions.

5. The separator according to any one of claims 1 to 4, wherein: The polymer further comprises an active group, and the active group is connected to the chelating group; Optionally, the active group includes at least one of a carboxylic acid group, an olefinic group, an epoxy group, a hydroxyl group and an aldehyde group.

6. The separator according to any one of claims 1 to 5, wherein: The volume average particle size Dv50 of the polymer is nanometer-scale; optionally, the volume average particle size Dv50 of the polymer is 50nm to 200nm; and / or The volume distribution particle size Dv90 of the polymer is 95 nm to 360 nm.

7. The separator according to any one of claims 1 to 6, wherein: The mass percentage of the polymer is 10% to 50% based on the mass of the functional layer.

8. The separator according to any one of claims 1 to 7, wherein: The coating weight of the functional layer is 1.0 g / m 2 Up to 3.5g / m 2 ; and / or The thickness of the functional layer may be 0.1 μm to 4 μm, and may be 0.5 μm to 3 μm.

9. The separator according to any one of claims 1 to 8, wherein: The functional layer also includes heat-resistant particles; Optionally, the mass percentage of the heat-resistant particles in the functional layer is less than or equal to 45%.

10. The separator according to any one of claims 1 to 9, wherein: The thickness of the substrate is less than or equal to 16 μm, and can be 5 μm to 14 μm; and / or The substrate includes a polyolefin-based polymer; optionally, the polyolefin-based polymer includes at least one of polyethylene, polypropylene and polyvinylidene fluoride.

11. A battery comprising the separator according to any one of claims 1 to 10.

12. An electrical device comprising the battery as claimed in claim 11.

Citation Information

Patent Citations

  • Modified separator, preparation method thereof and lithium ion battery

    CN109560238A

  • Diaphragm capable of capturing transition metal ions, and preparation method and application thereof

    CN113224460A

  • Diaphragm and battery containing diaphragm

    CN116345066A

  • Battery separator, its manufacture, and battery

    JP1999238496A

  • Catchment Pipe and Trench Drain Pipeline System for Manufacturing Method of the Same

    KR102360446B1